Latino Family Childcare Providers' Beliefs, Attitudes, and Practices Related to Promotion of Healthy Behaviors among Preschool Children: A Qualitative Study - Ana C. Lindsay; Judith A. Salkeld; Mary L. Greaney; Faith D. Sands (Hindawi Limited, 2015)
Background. The continuing rise of obesity among Latinos is a public health concern with an immediate need for early prevention. Changes in family structures have increased demand and reliance for child care for young children. Latino children are the fastest-growing segment of the child population in the United States, and research shows that Latino families use preschools and day care centers much less than those of other ethnic groups, apparently because of cultural preferences for family-like care. Objectives. Given that many low income Latino children attend family child care homes (FCCHs), there is a need to explore the role that FCCH providers may play in establishing and reinforcing children's early healthful eating and physical activity behaviors and consequently in the prevention of childhood obesity. Design. Using purposive sampling, six focus groups were conducted in Spanish with licensed Latino FCCH providers n=44. Data was analyzed to identify recurrent themes. Results. Latino FCCH providers described how they play an influential role in promoting healthful eating and physical activity behaviors of preschool children in their care. They also identified many barriers and challenges in establishing and maintaining healthful nutrition and physical activity behaviors, including high cost of healthy foods, cold weather, and physical environment of FCCH. Conclusions. Latino FCCH providers can have a strong impact in promoting healthful behaviors in low-income, Latino communities. They may be able to effectively deliver interventions targeting low-income, minority families to promote healthful eating and physical activity behaviors and prevent child obesity.